2012
DOI: 10.1002/pds.3349
|View full text |Cite
|
Sign up to set email alerts
|

Administered paricalcitol dose and survival in hemodialysis patients: A marginal structural model analysis

Abstract: Purpose Several observational studies have indicated that vitamin D receptor activators (VDRA), including paricalcitol, are associated with greater survival in maintenance hemodialysis (MHD) patients. However, patients with higher serum parathyroid hormone (PTH), a surrogate of higher death risk, are usually given higher VDRA doses, which can lead to confounding by indication and attenuate the expected survival advantage of high VDRA doses. Methods We examined mortality-predictability of low (>1 but <10 μg/w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 52 publications
(94 reference statements)
1
24
0
Order By: Relevance
“…According to a recent meta-analysis [45], there are only weak and imprecise correlations of drug effects on serum levels of phosphate, calcium, and PTH with all-cause and cardiovascular death in patients with CKD, suggesting that the drug's nonmineral actions favorably affected these clinical endpoints. The same has been suggested also by previous cohort studies in which the use of VDRAs [16][17][18][19][20][21] or the use of phosphate-binders [21,46] were associated with a lower risk of all-cause death, CVD death, or incident CVD in dialysis patients, even after adjusted for serum calcium, phosphate, and PTH levels. The J-DAVID study will reveal whether or not the VDRA treatment reduces CVD and/or mortality even when the current target ranges of phosphate, calcium, and intact PTH are respected.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…According to a recent meta-analysis [45], there are only weak and imprecise correlations of drug effects on serum levels of phosphate, calcium, and PTH with all-cause and cardiovascular death in patients with CKD, suggesting that the drug's nonmineral actions favorably affected these clinical endpoints. The same has been suggested also by previous cohort studies in which the use of VDRAs [16][17][18][19][20][21] or the use of phosphate-binders [21,46] were associated with a lower risk of all-cause death, CVD death, or incident CVD in dialysis patients, even after adjusted for serum calcium, phosphate, and PTH levels. The J-DAVID study will reveal whether or not the VDRA treatment reduces CVD and/or mortality even when the current target ranges of phosphate, calcium, and intact PTH are respected.…”
Section: Discussionsupporting
confidence: 80%
“…The use of activated vitamin D sterols, or vitamin D receptor activators (VDRAs), was reported to be associated with lower risk of all-cause mortality [16][17][18], CVD-related mortality [19,20], and incident CVD [21] in hemodialysis patients. Many, but not all [22], studies reported such associations as previously reviewed [23].…”
Section: Introductionmentioning
confidence: 99%
“…In previous studies, vitamin D analogs therapy was associated with favorable outcomes in CKD [29, 30] and dialysis patients. [3133] Active vitamin D therapy may impact outcomes independently of its effect on serum PTH. Patients having persistent high serum PTH tended to be continuously treated with high dose of active vitamin D, which could attenuate a harmful effect from uncontrolled serum PTH.…”
Section: Discussionmentioning
confidence: 99%
“…The percentages of patients censored for kidney transplantation and being loss to follow-up were 4% and 2%, respectively. The use of one set of censoring weights has been performed in the previous studies [21, 22]. Sensitivity analyses were conducted with consideration of censoring weights for transplantation, and loss to follow-up.…”
Section: Methodsmentioning
confidence: 99%